Status of Pig Rearing Practices in the Urban Districts of Uttarakhand (Indian Journal of Animal Production and Management, 2024)
Uttarakhand, a mountainous state located on  the southern slope of the Himalayas, relies heavily  on animal husbandry for its economy. However, the  piggery sector in the state is unorganized and  insufficient to meet the growing demand for pork.  Moreover, the increasing urbanization and  deforestation in the planar districts have blurred the  boundaries between wildlife, livestock and human  habitats. This study through a household survey  approach aims to determine the socio-economic  characteristics of the pig rearing community, the pig  husbandry practices they adopt and also assess the  ecological impacts of pig farming in urban districts  of Uttarakhand. 28 households were surveyed and  analysis of the result shows dismal socio-economic  condition of the pig rearing community.  Furthermore, 28.6% maintained breeding boar of  feral origin and 96.94% followed semi-intensive pig  rearing practices; hence human settlements have  stayed in close association with pigs (domestic and  wild) and other domestic animals. The possibility of  the emergence of zoonotic disease and its easy  transmission to humans has become more  prominent in the urban setting. The findings of this  study provide a preliminary picture of the current  status of pig husbandry practices and challenges  faced by piggery sector and government can take  into account these crucial insights for a holistic  piggery development program in the state.
Keywords: pig rearing practices; urban; Uttarakhand; socio-economic status